Novel Co(II), Ni(II) and Cu(II) complexes involving a 2-thienyl and trifluoromethyl containing symmetrically-substituted tetradentate Schiff-base ligand: Syntheses, structures, electrochemical and computational studies. (1st September 2018) - Ahumada, Guillermo; Fuentealba, Mauricio; Roisnel, Thierry; Kahlal, Samia; Carrillo, David; Cordova, Ricardo; Saillard, Jean-Yves; Hamon, Jean-René; Manzur, Carolina
Graphical abstract: The three new four-coordinate Co(II), Ni(II) and Cu(II) complexes featuring a symmetrical N2 O2 -tetradentate Schiff base ligand substituted with trifluoromethyl and 2-thienyl groups, adopt a square planar geometry (pictured). DFT and TD-DFT calculations were performed to rationalize structural, electrochemical and electronic parameters of the complexes. Abstract: Here, we report three novel metal(II) complexes (M = Co, 3a ; Ni, 3b ; Cu, 3c ) involving a symmetrically-substituted N2 O2 -tetradentate Schiff base ligand bearing trifluoromethyl and 2-thienyl substituents. Complexes 3a–c were readily synthesized upon reaction of the diprotic Schiff base proligand with the appropriate hydrated metal(II) acetates, and isolated as neutral, air and thermally stable solids in good to excellent yields (>65–85%). All the complexes have been well characterized using elemental analysis and different spectroscopic tools (ESI + HRMS, FT-IR, UV–Vis), and single crystal X-ray diffraction analysis for 3b and 3c . Their crystal structures revealed a four-coordinate square planar geometry at the Ni(II) and Cu(II) metal ions, with two nitrogen and two oxygen atoms as donors. Complexes 3a–c displayed similar cyclic voltammetric behavior, exhibiting one anodic and one cathodic wave, both irreversible and of different intensity. They were tentatively assigned to M(II)/M(III) and M(II)/M(I) redox couples, respectively. No deposits of polymeric films on the electrode surface were observed. Structural, electrochemical and electronic parameters of the complexes have been rationalized on the ground of DFT and TD-DFT computation.